Population Response Propagation to Extrastriate Areas Evoked by Intracortical Electrical Stimulation in V1 - Fehérvári, Tamás D.; Yagi, Tetsuya (Frontiers in Neural Circuits, 2016)
The mouse visual system has multiple extrastriate areas surrounding V1 each with a distinct representation of the visual field and unique functional and connectivity profiles, which are believed to form two parallel processing streams, similar to the ventral and dorsal streams in primates. At the same time, mouse visual areas have a high degree of interconnectivity, in particular V1 sends input to all higher visual areas. The study of these direct connections can further our understanding of the cortical processing of visual signals in the early mammalian cortex. Several studies have been published about the anatomy of these connections, but an in vivo electrophysiological characterization and comparison of the transmission to multiple extrastriate areas has not yet been reported. We used intracortical electrical stimulation combined with RH1691 VSD imaging in adult C57BL/6 mice in urethane anesthesia to analyze interareal transmission from V1 to extrastriate areas in superficial cortical layers. We found 7 extrastriate response sites (5 lateral, 2 medial) in a spatial pattern similar to area maps of the mouse visual cortex and, by shifting the location of V1 stimulation, demonstrated that the evoked responses in LM and AL were in accordance with the visuotopic mappings of these areas known from anatomy and in vivo studies. These two sites, considered to be gateways to their processing streams, had shorter latencies and faster transmission speeds than other extrastriate response sites. Short latency differences between response sites, and that TTX injection into LM reduced but did not eliminate other extrastriate responses indicated that the evoked cortical activity was, at least partially, transmitted directly from V1 to extrastriate areas. This study reports on analysis of interareal transmission from V1 to multiple extrastriate areas in mouse using intracortical electrical stimulation in vivo.